Wholesome dwellings housing need in Oxford and the municipal response, 1800-1939 - Graham, Malcolm 1948- (Archaeopress Publishing Ltd, 2020)
This study by Malcolm Graham, a leading Oxford local historian for many years, provides an insight into post-war housing needs in Oxford, and how the modern city evolved away from the university buildings and college quadrangles for which the city is internationally renowned
Keywords: Geschichte 1800-1039; Gesundheit; Wohnen; Oxford; Public housing / England / Oxford / History / 20th century; Oxford (England) / Social conditions / 20th century